The Relationship of Financial Literacy and Financial Inclusion in Attracting Student Interest to Become Customers Syariah Banking - An Ras Try Astuti (Journal of Accounting and Finance Management, 2023)
The presence of students in the world of Islamic banking as a young generation provides an opportunity for banks to continue to exist in the midst of existing competition. This study investigates how the influence of financial literacy and Islamic financial inclusion in attracting customer interest from among students. This research uses a type of quantitative research with statistical data. The number of respondents was 144 respondents who were students of the Islamic banking study program at the Parepare State Islamic Institute and Parepare Muhammadiyah University. Data analysis technique is a process used to manage research results in order to obtain a conclusion. Statistics is knowledge about data collection, data classification, data presentation, data management, drawing conclusions and making decisions based on certain problems. one sample t test, multiple linear regression test. Partial Test (t test), Simultaneous F Test and Coefficient of Determination Test. The results of the Financial Literacy research show that from the sample calculation values ??above, it is found that the average financial literacy is 43.2% of what is expected. Thus financial literacy is in the good category. Financial inclusion, shows that from the sample calculation value above, it is found that the average financial inclusion = 28.8% is in the good category. Interest in Using Islamic Financial Institutions, shows that from the sample calculation value above it is found that the average financial literacy is 21.6% of what is expected. The correlation coefficient is 0.804 with a significance of 0.000. Because the significance is 0.000 <0.05, Ho is rejected and H1 is accepted. This means that there is a positive and significant relationship between financial literacy and inclusion on the interest of Islamic Banking students at IAIN Parepare and Muhammadiyah Parepare University. The effect of financial literacy and inclusion on student interest in using Islamic financial institutions is 0.804. The calculated F-value is 62,932 with a significance level of 0.000. Because the P-Value <0.05, Ho is rejected or in other words the coefficients ?1 and ?2 affect Y together so that it can be said that the regression model.